Pengembangan Panduan Teknik Coping Stress Untuk Mengurangi Kecemasan Akademik Siswa Pasca Era Pandemi - Cahyaningrum, Vesti Dwi; Da’i, Mohamad (Universitas Nusantara PGRI Kediri, 2023)
In 2020 the whole world experienced an outbreak, namely the Covid-19 pandemic which had an impact on various fields, one of which was in education. One of the effects is that students experience a lot of academic anxiety. Academic anxiety is widely felt by students who are affected by online schools and require them to stay at home and limit their space for movement, one of which is not being able to meet face to face with friends or teachers. One of the things that are planned to be able to reduce academic anxiety is by using stress coping techniques. Coping stress is an action or effort taken to overcome stress, which can be done both consciously and unconsciously. This study aims to produce a guidebook for providing stress coping techniques to reduce students' academic anxiety. The method used in this study is a research and development model. The subject of this research trial involved guidance and counseling experts;Education technologist;and school counselor. The instrument used is the student's academic anxiety scale,expert assessment instrument and counselor assessment instrument. Data from the assessment results of a BK expert, a TEP expert, and three school counselors in three different schools in Bojonegoro City indicate that the product developed is acceptable and feasible to use to reduce students' academic anxiety.